1995
DOI: 10.1002/art.1790080208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community arthritis program in Australia: Dissemination of a developed program

Abstract: Objective. To evaluate the effectiveness of a community-based arthritis education program conducted in a number of locations throughout the Sydney, Australia, metropolitan area.Methods. The program, based on earlier work, comprised 6 weekly sessions of 2.5 hours' duration. The study sample included 275 men and women with different types of arthritis, divided into intervention (n = 204) and control (n = 71) groups. Five outcome measures were selected to evaluate effectiveness of the program: pain perception, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…2003). However, our results are in contrast to previous findings about pain rating (Simeoni et al. 1995, Barlow et al.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2003). However, our results are in contrast to previous findings about pain rating (Simeoni et al. 1995, Barlow et al.…”
Section: Discussioncontrasting
confidence: 99%
“…2003, Siu & Chui 2004). However, there were no statistically significant increases in exercise practice for some arthritis self‐management programmes (Simeoni et al. 1995, Lindroth et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…30 , 31 Our observation that older age, presence of comorbid chronic conditions, and poor self-rated health are associated subsequent ADL deterioration is in agreement with previous research. 3 , 15 , 28 , 3138 Moreover, our data indicate that these 3 factors and their timing have different epidemiologic roles in the risk of arthritis. As noted above, we found that older age, presence of comorbid chronic conditions, and poor self-rated health were the only predictors of ADL disability at baseline.…”
Section: Discussionmentioning
confidence: 72%
“…33 Studies have also shown that arthritis patient education programs can be useful for enhancing self-care management techniques and improving physical and psychological health outcomes. 37 , 38 Furthermore, it has been reported that becoming widowed and the duration of widowhood are important determinants for the onset of late-life disability in different disability domains. 39 , 40 Previous study results have also highlighted the importance of focusing not only on the short-term effects of socioeconomic factors, but also on the possibility of long-term effects on disability in older adults.…”
Section: Discussionmentioning
confidence: 99%